Analisis ROA, ROE dan NPM Terhadap Harga Saham Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia - Melinda Melinda; Hermaya Ompusunggu (eCo-Buss, 2022)
The motive in this research is to analyze and determine the effect of Return on Assets, Return on Equity and Net Profit Margin on stock prices in manufacturing companies listed on Indonesia Stock Exchange from 2016-2020. The population are consumer goods industrial companies listed on the BEI with 61 companies. The sampling technique is use purposive sampling and the criteria for sampling is 26 companies. This reseach get the data is from secondary data in the form of manufacturing company reports. Data collection techniques using financial report documentation from www.idx.co.id. The data obtained by SPPS version 25. The data analysis technique used descriptive statistical analysis, classical assumption test, multiple linear analysis and hypothesis. The results of the research show that the variables of return on assets, return on equity and net profit margin have an influence on stock prices. Furthermore, return on assets has a negative and significant effect on stock prices. Meanwhile, return on equity and net profit margin have a significant and positive impact on the shares of manufacturing companies in the consumer goods industry which are listed on Indonesia Stock Exchange during 2016-2020